Frequency support using doubly fed induction and reluctance wind turbine generators. (October 2018) - Attya, A.B.; Ademi, S.; Jovanović, M.; Anaya-Lara, O.
Highlights: Two wind turbine technologies are enabled to use two methods of frequency support. Prominent BDFRG is compared to the prevailing DFIG when providing this ancillary service. From power system application perspective, the BDFRG and the DFIG are aligned. Impact of support method and generator technology on system inertia is quantified. Abstract: This paper presents the comparative computer simulations of a commercial doubly-fed induction generator (DFIG) and an emerging brushless doubly-fed reluctance generator (BDFRG) for grid-connected wind turbines in terms of frequency support based on the inertia emulation and blade pitching de-loading. The BDFRG features the low operation and maintenance cost by using a fractional inverter, and offers the high reliability of brushless structure with a simpler, more compact 2-stage gearbox design while still ensuring competitive performance to its popular slip-ring companion. The implemented benchmark is carefully designed to ascertain the relative capabilities of the two wind turbine generator technologies in providing this ancillary service. The results reveal that in spite of the fundamentally different operating principles, the DFIG and the BDFRG are highly aligned from the viewpoint of power system applications.